RELIGIOUS CONSCIOUSNESS AS A PILLAR OF PERFORMANCE IMPROVEMENT: A STUDY ON EMPLOYEES OF UIN ALAUDDIN MAKASSAR - Nurfatimah, Nurfatimah; Supardin, Supardin (Idaarah: Jurnal Manajemen Pendidikan, 2024)
This study explores the effect of religious awareness on employee performance at the State Islamic University of Alauddin Makassar. In the context of Islamic educational institutions, religious awareness is a fundamental value that is expected to improve the productivity and quality of employee performance. Using a correlational quantitative approach, this study involved 66 employee respondents who were selected through a simple random sampling method. Data were collected using a structured questionnaire that evaluated two main variables: religious awareness as the independent variable and performance as the dependent variable. The results of data analysis showed a significant positive relationship between religious awareness and better employee performance, especially in the aspects of Islamic work ethics, punctuality, and commitment to duty. This finding implies the importance of religiosity in building productive work behavior and integrity. Therefore, strengthening religious programs for employees can be a strategy to strengthen and improve performance, which in turn can support the development of performance improvement policies based on religious values in Islamic educational institutions.